2017
DOI: 10.1158/2326-6066.cir-16-0249
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Efficacy of 4-1BB Costimulation Is Abrogated by PD-1 Blockade in a Model of Spontaneous B-cell Lymphoma

Abstract: Combinations of mAbs that target various components of T-cell activation/inhibition may work synergistically to improve antitumor immunity against cancer. In this study, we investigated the therapeutic potential of combining an anticancer vaccination strategy with antibodies targeting an immune stimulatory (4-1BB) and immune inhibitory (PD-1) receptor, in a preclinical model of spontaneously arising c-Myc-driven B-cell lymphoma. In Eμ-myc transgenic mice, we reveal that 4-1BB agonistic mAb treatment alone was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 18 publications
0
32
0
Order By: Relevance
“…In a model of B cell lymphoma, McKee et al recently demonstrated an abrogation of the therapeutic effect of 4-1BB costimulation when anti-PD-1 was combined concurrently (43). In our studies, concurrent anti-OX40 and anti-PD-1 also attenuated anti-OX40-induced therapeutic efficacy, dramatically increased serum cytokine levels, and increased peripheral T cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…In a model of B cell lymphoma, McKee et al recently demonstrated an abrogation of the therapeutic effect of 4-1BB costimulation when anti-PD-1 was combined concurrently (43). In our studies, concurrent anti-OX40 and anti-PD-1 also attenuated anti-OX40-induced therapeutic efficacy, dramatically increased serum cytokine levels, and increased peripheral T cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…These results are disappointing given the promising potential of combining CD137 stimulation with PD-1/PD-L1 blockade in solid tumors (33). Nevertheless, it was recently reported that PD-1 blockade abrogates the therapeutic efficacy of anti-CD137 mAbs in the Eμ-MYC model of mouse lymphoma (34). In agreement with this report, our data emphasize the need for a better understanding of the underlying immune responses to combi-nation therapies to define the specific cancer types and conditions where they might be beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 Interestingly, however, a study by Messenheimer et al found that when a-OX40 and a-PD-1 antibodies were administered sequentially by treating MMTV-PyMT tumor-bearing mice with a-OX40 mAb before a-PD-1 mAb, the sequential combination therapy resulted in augmented antitumor efficacy. 25 The reason for the discrepancies observed between different studies involving checkpoint inhibitor and immune agonist combination is not completely understood; however, the dose and timing of the immune-modulating antibody administration may be of high importance. 23 Further, another study that tested the combination of a-4-1BB and a-PD-1 antibodies in a murine spontaneous B-cell lymphoma model found that simultaneous use of a-PD-1 mAb diminished the antitumor activity of a-4-1BB mAb alone.…”
Section: Using Immunomodulatory Antibodies To Enhance Car T-cell Antimentioning
confidence: 99%
“…The mechanism for this effect was thought to be due to a dramatic reduction in the function of effector CD8 + T cells in the presence of a-PD-1 mAb, potentially through induced apoptosis. 25 The reason for the discrepancies observed between different studies involving checkpoint inhibitor and immune agonist combination is not completely understood; however, the dose and timing of the immune-modulating antibody administration may be of high importance.…”
Section: Using Immunomodulatory Antibodies To Enhance Car T-cell Antimentioning
confidence: 99%